Pemilihan Merek Mie Instan Bagi Mahasiswa Institut Teknologi Dan Bisnis Riau Pesisir Metode Analytical Hierarchy Process (AHP) - Finna Varenty; Trisna Mesra; Naufal Dinata Hidayat; M Ali Akbar; Aulia Rahma Yanti; Yolandha Natasya; SF Imanuel Hutagalung (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Selecting an instant noodle brand is a challenging decision-making process, as it involves numerous considerations. A systematic and objective approach is essential. This study utilizes four primary criteria for assessment: taste, price, packaging, and brand image. The brand alternatives analyzed included Indomie, Mie Sedaap, Sarimi, and Supermi. Data were collected through a questionnaire distributed to 30 student respondents using a purposive sampling technique. The analysis showed that the brand criterion had the highest importance weighting of 0.4 (40%), followed by packaging, price, and taste. The preference scores for each alternative were determined using the Analytical Hierarchy Process (AHP) method. Based on the calculation, the Supermi brand achieved the highest preference score of 0.44 and was ranked first. Sarimi was in second place with a score of 0.34, followed by Mie Sedaap with a score of 0.16, and Indomie was ranked last with a score of 0.06. The AHP method has been shown to facilitate structured, consistent, and objective decision-making.